Exploring Curricular and Cocurricular Effects on Civic Engagement at Emerging Hispanic-Serving Institutions. Issue 4 (April 2018) - Garcia, Gina A.; Cuellar, Marcela
Background/Context: Hispanic-Serving Institution (HSIs), or those postsecondary institutions that meet the 25% Latina/o enrollment requirement to become federally designated as HSIs, are burgeoning in the United States. Similarly, emerging Hispanic-Serving Institutions (eHSIs), or those postsecondary institutions that enroll between 15% and 24% Latina/o students, are rapidly increasing. As these institutions increase in number, there is a need to understand them as unique organizations that provide distinct outcomes for diverse students, including students of color, commuter students, and low-income students. Purpose/Objective/Research Question/Focus of Study: The purpose of this study was to explore the ways in which eHSIs contribute to one specific outcome, civic engagement. We conceptualized civic engagement as primarily defined by political involvement (contacting public officials, participating in a political demonstration, discussing politics, voting in an election), although volunteerism was also included in our definition (engaging in community service). The main research question guiding this study was: What curricular and cocurricular experiences contribute to the civic engagement of students enrolled at eHSIs? Population/Participants/Subjects: A sample of 10, 022 students was drawn from the Cooperative Institutional Research Program (CIRP). The sample is inclusive of women (61%), first-generation college students (18%), and racially diverse individuals, including Latina/o (18%), Black (4%), Asian/Pacific Islander (38%), American Indian (4%), and White (51%). Research Design: We used a cross-sectional research design, measuring the civic engagement of students enrolled at six eHSIs at one time point. Secondary data came from CIRP's Diverse Learning Environments (DLE) survey, which focuses on the experiences of diverse students and their perceptions of the climate and institutional practices for diversity. Data Collection and Analysis: The DLE survey is web based and administered annually by the Higher Education Research Institute (HERI). We merged two data sets, the 2010 and 2011 DLE, data from the 2010–2011 Integrated Postsecondary Education Data System (IPEDS), and information about diversity-related curricula and cocurricular programs for each of the six institutions. We ran t tests and used ordinary least squares regression to examine relationships between variables. Findings/Results: Findings show that students' perceptions of their academic validation and of a curriculum of inclusion in the classroom, as well as their involvement in campus-facilitated diversity programs, positively predict their civic engagement. Recommendations: Recommendations for research include developing and validating quantitative measures of civic engagement for diverse students attending compositionally diverse institutions. Recommendations for practice include acknowledging the changing demographics within postsecondary institutions and creating curricular and cocurricular structures that will contribute to nonacademic outcomes such as civic engagement.